2017
DOI: 10.1097/inf.0000000000001521
|View full text |Cite
|
Sign up to set email alerts
|

Successful Introduction of Fine Needle Aspiration Biopsy for Diagnosis of Pediatric Lymphadenopathy

Abstract: Accurate and rapid diagnosis of extrapulmonary nodal tuberculosis in children is of paramount importance. This retrospective study performed at Tygerberg Hospital using data from the laboratory records between January 1, 2004 and June 30, 2014 demonstrates how since the introduction laboratory-run FNAB service; fine needle aspiration biopsy has become an acceptable and routine diagnostic procedure for triage of pediatric lymphadenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The use of fine-needle aspiration to obtain pus and tissue samples from various body sites, including mediastinal lymph nodes, spleen, and prostate, has been reported to have enabled confirmation of melioidosis infections [ 15 17 ]. This minimally invasive technique may be particularly useful for difficult to access sites and when surgical biopsies are not possible or available [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of fine-needle aspiration to obtain pus and tissue samples from various body sites, including mediastinal lymph nodes, spleen, and prostate, has been reported to have enabled confirmation of melioidosis infections [ 15 17 ]. This minimally invasive technique may be particularly useful for difficult to access sites and when surgical biopsies are not possible or available [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the past few years, several studies have confirmed the diagnostic utility of FNAB in cancer, and therefore, it is now widely used in clinical practice. [2][3][4][5][6][7][8][9][10][11] Owing to innovative developments in FNA technology, we can now collect more cells to prepare cell blocks (CB) that can be used for cell smears and immunohistochemistry (IHC) staining analysis, which compensates for some of the shortcomings of simple smears in organisational structure and cell morphology. IHC analysis represents an important technique to improve the accuracy of FNAB diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…IHC analysis represents an important technique to improve the accuracy of FNAB diagnoses. 4,5,8,12,13 In this study, we aimed to explore the feasibility of the combination of IHC analysis and Epstein-Barr virus (EBV)-encoded small RNAs (EBERs) in situ hybridisation of CB sections prepared via FNA for diagnosing metastatic lymph nodes from nasopharyngeal carcinoma (NPC) and comparing this method with simple cell smears and cell smears combined with CBs prepared via FNAB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations